A robust numerical method for modeling ventilation through long tunnels in high temperature regions based on 1D pipe model. (September 2021) - Zhao, Zhihong; Xu, Haoran; Liu, Guihong; Liu, Feng; Wang, Guiling
Highlights: Simplified 1D model for air flow and heat transfer in long tunnels is proposed. Good agreement between numerical and indoor lab results verifies the proposed model. Effect of ventilation on air and rock temperatures is investigated by a case study. Abstract: A robust numerical model, which can simulate the coupled air flow and heat transfer processes in long tunnels, is essentially required to design and operate the mechanical ventilation system in long tunnels surrounded by high temperature rocks. Due to the extreme scale disparity between tunnel diameter and length (~m vs. ~km), very fine mesh is required to accurately represent the highly-dynamic surrounding rocks near the tunnel, and thus the conventional numerical method is usually time consuming. To improve the computational efficiency without losing accuracy, a simplified one-dimensional tunnel model considering heat convection and conduction along tunnel axis and heat transfer between air in the tunnel and the surrounding rocks in the radial direction is proposed. A laboratory test of a high temperature tunnel with longitudinal ventilation is used to examine the reasonability and efficiency of the proposed modeling method. The good agreement between numerical and experimental results demonstrates that the developed ventilation modeling method is a robust simulation tool for design and management of mechanical ventilation system in a long tunnel. The effects of mechanical ventilation parameters and insulation layer thickness on the temperatures of air in the tunnel and surrounding rocks around the tunnel are investigated based on a case study of the planned Zheduo mountain tunnel, China.